2004
DOI: 10.1063/1.1827345
|View full text |Cite
|
Sign up to set email alerts
|

Pulse propagation in adiabatically coupled photonic crystal coupled cavity waveguides

Abstract: A rigorous analysis of pulse propagation in planar photonic crystal (PhC) coupled cavity waveguides (CCWs) of finite length is reported. Conventional PhC waveguides, formed by a single line defect, are used at both interfaces of the CCW. An adiabatic taper based on progressively varying the radii of the spacing defects between cavities is used to achieve flat transmission bands with respect to the butt coupling case. The influence on the main parameters of the propagated pulse such as group delay, full width a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This CCW is coupled to line defect waveguide (LDWG) at either ends to facilitate integration with external devices. Different schemes of coupling between CCW and LDWG have been reported earlier [8]- [9]. After analyzing these schemes, we observed that for our waveguide design, the overall power transmission was maximum when two extra air holes were placed at these interfaces probably due to the effect of adiabatic transition.…”
Section: A Pc Lattice and The Defect Microcavitymentioning
confidence: 82%
“…This CCW is coupled to line defect waveguide (LDWG) at either ends to facilitate integration with external devices. Different schemes of coupling between CCW and LDWG have been reported earlier [8]- [9]. After analyzing these schemes, we observed that for our waveguide design, the overall power transmission was maximum when two extra air holes were placed at these interfaces probably due to the effect of adiabatic transition.…”
Section: A Pc Lattice and The Defect Microcavitymentioning
confidence: 82%
“…The undesired resonance peaks are eliminated by the introduction of the adiabatic taper in the structure. The underlying physics of the taper is an adiabatic matching of the dispersion relations of the SLWG and the CCW [3].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…An adiabatic coupling technique between single-line-defect waveguides (SLWGs) and CCWs was recently proposed [2]. Furthermore, their dynamic performance by analyzing the transmission of ultrashort pulses through the structure was also investigated [3]. The coupling technique is based on gradually varying the radii of the spacing defects between cavities, as it can be seen in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An adiabatic coupling technique between single-line defect waveguides (SLWGs) and CCWs was recently proposed [5]. Furthermore, the dynamic performance was also investigated by analyzing the transmission of ultrashort pulses through the structure [6]. The coupling technique is based on gradually varying the radii of the spacing defects between cavities in order to match the SLWG and CCW modes.…”
Section: Introductionmentioning
confidence: 99%